Coherence and Processes of Interpretation: Implicature - Imamov N. P.; Karimova M. Ya. (Researchparks Publishing, 2022)
The given article is devoted to the study of comparison and their interpretation of pragmatic and semantic meaning. Meaning is one of the most controversial terms in the theory of language. And at first glance it seems that understanding this term does not cause any difficulties - it is freely used in teaching, interpretation and translation. As for the analysis of some kind of context or text, it is faced with the problem of various types, such as word-meaning and its lexical, grammatic, semantic, pragmatic and stylistic meanings.